Wo ai ni Mommy - Wang-Breal, Stephanie (POV ; American Documentary, 2009)
Verzio FF Submission From 2000 to 2008, China was the leading country for U.S. international adoptions. There are now approximately 70,000 Chinese children being raised in the United States. Wo Ai Ni Mommy explores what happens when an older Chinese girl is adopted into an American family. In 2007 Donna and Jeff Sadowsky of Long Island, New York submitted their dossier to adopt eight-year old Fang Sui Yong from Guangzhou, China. From the very first moment Sui Yong meets her new mother, Donna, we get a real sense of the emotional confusion and loss Sui Yong experiences, as adoption workers translate their first words of communication. This day will change Sui Yong’s life, forever. Language, habits, food, everything she knows will never be the same. Her new life in America is filled with happiness and confusion. As she struggles to survive in this new world, we witness her transform into a lively, outspoken American. Sui Yong has become someone neither she nor Donna could have imagined. In a sense, she’s the same girl Donna met in Guangzhou all those months ago – and yet she’s utterly different.